Pengaruh Model Contextual Teaching And Learning (CTL) Terhadap Hasil Belajar Siswa Kelas XI Di SMA Negeri 1 NA IX-X - Nova Elza; Erlia Utami Panjaitan; Syahraini Ritonga (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This study aims to determine the effect of Contextual Teaching and Learning (CTL) method, on the learning outcomes of students at SMA Negeri 1 NA IX-X. This study used two classes, namely experimental class and control class. The research sample consisted of two groups, namely the experimental class namely XI-3 with the number n = 30 and the control class namely XI-2 with the number n = 30 which used conventional methods. Data collection was carried out through the form of a total of 30 learning outcome tests. Data analysis used t-test statistical test to determine the difference in learning outcomes between the two groups. Thus, this study proved effective in improving the learning outcomes of students at SMA Negeri 1 NA IX-X Labuhanbatu Utara. The average pretest score of the Experiment class was 65.1 and on the posttest it increased to 86.1, showing an increase of 21 points. Meanwhile, the control class using only conventional methods only experienced an increase from 64.2 to 72.1, an increase of 7.9. The results of the t-count hypothesis 14.00> t-table 2.00 with a significant level (0.05 = 5%) it can be concluded that H0 is rejected and Ha is accepted in other words that there is a significant effect with the learning model with the Contextual Teaching and Learning (CTL) method.